2004
DOI: 10.1523/jneurosci.2376-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Sex Discrimination Persists, Whereas the Preference for Urinary Odorants from Estrous Females Disappears in Male Mice after Vomeronasal Organ Removal

Abstract: Based on observed changes in the social context for the display of ultrasonic vocalizations, scent marking, aggression, and mounting behavior by male mice with a null mutation of the transient receptor potential 2 ion channel, it was proposed recently that a primary function of the mouse vomeronasal organ (VNO)/accessory olfactory system is sex discrimination. We tested this hypothesis directly by studying the ability of male mice to discriminate between urinary odors of conspecifics of the two sexes and in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
197
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(223 citation statements)
references
References 29 publications
24
197
0
2
Order By: Relevance
“…Complimentary to the results detailed previously, surgical lesions of the VNO clearly showed that this treatment is not effective in disrupting mate recognition in both male and female mice [44,45,82,83]. Indeed, VNO-lesions did not impair the discrimination of body or urinary volatile odorants in a habituation/dishabituation test as well as the preference for opposite-sex-derived volatile odors measured in Y-maze choicetests.…”
Section: Olfactory Control Of Mate Recognitionsupporting
confidence: 58%
See 1 more Smart Citation
“…Complimentary to the results detailed previously, surgical lesions of the VNO clearly showed that this treatment is not effective in disrupting mate recognition in both male and female mice [44,45,82,83]. Indeed, VNO-lesions did not impair the discrimination of body or urinary volatile odorants in a habituation/dishabituation test as well as the preference for opposite-sex-derived volatile odors measured in Y-maze choicetests.…”
Section: Olfactory Control Of Mate Recognitionsupporting
confidence: 58%
“…In the male, the involvement of VNO in copulatory behavior seems to vary according to the species. In male mice, lesioning the VNO is without any impact on male sexual behavior [82] and Trp2-KO male mice also show normal levels of copulation [105]. These results point to a possible role for the main olfactory system in the expression of male sexual behavior [45].…”
Section: Olfactory Control Of Sexual Behaviormentioning
confidence: 74%
“…Male mice show a preference for female urine over male urine (29). We tested whether this sexual preference is maintained in ΔD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies (reviewed in Pankevich et al, 2004) suggest that sex discrimination and resultant heterosexual mate recognition in many non-primate mammals rely on the detection and processing of body odors by the main olfactory system. For example, in the ferret, the induction of anosmia by occlusion of the main olfactory epithelium eliminated the preference of both male and female subjects to approach tethered opposite-sex conspecifics in Y-maze tests (Kelliher and Baum, 2001).…”
Section: Introductionmentioning
confidence: 99%